2018
DOI: 10.2147/idr.s150005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of carbapenem-resistant Gram-negative bacilli clinical isolates in Algeria

Abstract: ObjectivesThe aims of this study were to investigate the occurrence of carbapenem-resistant Gram-negative bacilli (GNB) isolated from inpatients and outpatients in Algeria between July and September 2015, and to screen their resistance mechanisms and genetic relatedness.Materials and methodsA total of 68 non-redundant isolates were identified using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) antibiotic susceptibility testing was performed using disk diffusion and Etest methods. Carba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
26
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 36 publications
15
26
3
Order By: Relevance
“…We could also note that ST48 was previously detected in an urban wastewater treatment plant in Algeria. 45 Moreover, in our study, 20.7% of CPKP strains producing NDM-1 belonged to ST101, a widespread clone diffused in Algeria, [46][47][48] but always associated with bla OXA-48 . The association between ST101 and NDM-1 producers was recently described in Tunisia, 49 Italy, 50 and Pakistan.…”
Section: Discussionsupporting
confidence: 47%
“…We could also note that ST48 was previously detected in an urban wastewater treatment plant in Algeria. 45 Moreover, in our study, 20.7% of CPKP strains producing NDM-1 belonged to ST101, a widespread clone diffused in Algeria, [46][47][48] but always associated with bla OXA-48 . The association between ST101 and NDM-1 producers was recently described in Tunisia, 49 Italy, 50 and Pakistan.…”
Section: Discussionsupporting
confidence: 47%
“…Carbapenemase enzymes are the most common mechanism by which resistance to carbapenems arises [ 8 , 9 ]. Carbapenem resistance has been labelled in Enterobacteriaceae , mostly in Klebsiella pneumoniae compared to Escherichia coli or other Enterobacterial species, and in non-fermentative Gram-negative bacilli such as Pseudomonas aeruginosa and Acinetobacter baumannii [ 4 ]. These Gram-negative bacteria are the main nosocomial pathogens and the most prevalent bacteria responsible for a range of hospital-acquired and community-acquired difficult to treat infections such as meningitis, pneumonia, peritonitis, septicaemia and urinary tract infections.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CPPA among total isolates identified among all studies in North Africa ranged from 0% (0/9 [ 22 ], 0/80 [ 24 ]) to 84% (28/33) [ 37 ] while it ranged from 2.3% (25/1077) [ 52 ] to 21.4% (9/42) [ 51 ] in East Africa. Among carbapenemase enzymes, VIM was highly detected along with CPPA isolates in the reported African countries.…”
Section: Resultsmentioning
confidence: 99%
“…This is not surprising, since OXA-23 has been found around the world [ 69 75 ]. Importantly, in Africa (particularly in North Africa), studies showed that bla OXA-23 is associated with IS Aba1 elements [ 13 , 31 , 76 ] and predominantly belongs to clone ST2 [ 22 , 23 , 31 , 76 78 ], which may enable rapid transmission among OXA-23-producing A. baumannii clinical isolates.…”
Section: Discussionmentioning
confidence: 99%